Addiction pharmacogenetics: a systematic review of the genetic variation of the dopaminergic system. (October 2015) - Patriquin, Michelle A.; Bauer, Isabelle E.; Soares, Jair C.; Graham, David P.; Nielsen, David A.
Abstract : Substance use disorders have significant personal, familial, and societal consequences. Despite the serious consequences of substance use, only a few therapies are effective in treating substance use disorders, thus highlighting a need for improved treatment practices. Substance use treatment response depends on multiple factors such as genetic, biological, and social factors. It is essential that each component is represented in treatment plans. The dopaminergic system plays a critical role in the pharmacotherapy for addictions, and an understanding of the role of variation of genes involved in this system is essential for its success. This review adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement guidelines. A computerized literature search was conducted using PubMed and Scopus (all databases). Articles published up to April 2015 that examined the role of dopaminergic gene variation in the pharmacotherapy of alcohol, opioid, and cocaine use disorders were reviewed. Search terms were dopamine, gene, polymorphism, substance abuse, treatment, and response. Polymorphisms of the DRD2, ANKK1, DAT1, DBH, and DRD4 genes have been found to moderate the effects of pharmacotherapy of alcohol, opioid, and cocaine use disorders. The integration of genetic information with clinical data will inform health professionals of the most efficacious pharmacotherapeutic intervention for substance use disorders. More studies are needed to confirm and extend these findings.